New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae) - Sites, Robert W.; Rodrigues, Higor D. D.; Reynoso-Velasco, Daniel (Zootaxa, 2017)
The Neotropical saucer bug species Ambrysus maldonadus La Rivers and Ambrysus montandoni La Rivers originally were placed in Ambrysus Stål despite aberrant physiognomies and features inconsistent with the genus. These two species are herein transferred from Ambrysus to Carvalhoiella De Carlo and are new combinations. Further, Ambrysus (Picrops) usingeri La Rivers represents a monotypic subgenus, which is herein elevated to full generic status. As such, Picrops usingeri represents a new status for this species and a second species of Picrops from the Guiana Shield is described. In addition, the male of Ambrysus brunneus Sites is described and a comparison of character states for genera of Ambrysini is provided.